(untitled) (Journal of Engineering, 2007)
Experiments were carried out to study the local and average heat transfer by natural convection in a vertical concentric cylindrical annulus. The experimental setup consists of an annulus has a radius ratio of 0.555 and inner cylinder with a heated length 1.2m subjected to the constant heat flux while the outer cylinder is subjected to the ambient temperature. The investigation covers heat flux range from 58.2 W/m2 to 274.31 W/m2 . Results show an increase in the natural convection as heat flux increases leads to an improve in the heat transfer process. An empirical equation of average Nusselt number as a function of Raylieh number was deduced .